An investigation of the effects which using the word processor has on the writing of standard six pupils - McKenzie, Donald John (Rhodes University, Faculty of Education, Department of Education, 1994)
In order to discover to what extent the use of the word processor affects the motivation of high school students when engaged in writing tasks, and to determine the effects of the word processing on the length and quality of their work and editing, two groups, carefully matched in terms of prior computer experience, intelligence and language ability were given eight writing tasks. The test group used word processors while the control group used pen and paper. Their behaviour was closely observed and their writing was subsequently compared. It was found that while the test group were more motivated and spent longer both writing and editing their work, the quality of the work of both groups was similar. The degree of editing was greater for the test group. The conclusion is that there is a place for the use of the word processor in the English classroom, but specific strategies need to be developed to optimise its benefits.
Keywords: Written communication -- Study and teaching -- Data processing; Word processors in education; Language arts -- Computer-assisted instruction; English language -- Writing--Study and teaching